ДРУГА СВІТОВА ВІЙНА В УСНИХ ІСТОРІЯХ БОЛГАР ПІВНІЧНОГО ПРИАЗОВ’Я (Zaporizhzhia Historical Review, 2021)
In this article the author broaches questions of broad introduction of oral history methodin the process of studying the problems of World War II in southern Ukraine. Detailed studying of Northern Priazovye Bulgarian oral stories showed wide possibilities of oral sources in socio-humanitarian reseaches of society structure during the crisis. The results of this work reflect necessity of more profound studying of daily routine questions and social and cultural relations not only in separate ethnic groups but also all region of southern Ukraine during the period of German occupation.